Comparison of Oncological Outcomes After Colorectal Cancer Surgery in Patients Undergoing Laparoscopic Versus an Open Procedure - Ul Haq, Qazi Tafheem; Ashrat, Muhammad Ayub; Ali, Usman Bin; Ghani, Usman; Razzaque, Hasnain; Saleem, Saadan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the oncological outcomes after colorectal cancer surgery in patients undergoing laparoscopic versus open procedures for colorectal carcinoma.Study Design: Comparative Cross-sectional Study.Place and Duration of Study: Surgical Department Combined Military Hospital, Rawalpindi and Histopathology Department Armed Forces Institute of Pathology Rawalpindi Pakistan, from June 2021 to March 2022.Methodology: This study was conducted on 60 patients who underwent oncological surgery for colorectal cancer via the open or laparoscopic method. Data were collected for all the patients from the Histopathology Department regarding proximal margin involvement, circumferential margin involvement, distal margin involvement, tumour perforation and lymph nodes resected. These parameters were compared in patients undergoing open or laparoscopic methods.Results: Out of 60 patients included in the final analysis, 41(68.3%) were males, and 19(31.7%) were females. The mean age of patients who underwent open or laparoscopic surgery for colorectal cancer in our study was 44.67±7.537 years. 32(53.3%)patients underwent laparoscopic surgery, while 28(46.7%) underwent an open surgical procedure. Statistical tests revealed that both Groups found that proximal margin involvement, circumferential margin involvement, distal margin involvement,tumour perforation, and the number of lymph nodes resected were not statistically significant (p-value>0.05).Conclusion: Oncological outcomes on histopathology were not different in patients undergoing the open or laparoscopic procedure. Therefore, laparoscopic colonic resection is oncologically equivalent to open resection.